Proposing Asian and African Motherhood through Literature: A Comparative Analysis - Triwahana Triwahana; Desca Angelianawati (Indonesian Journal of English Language Studies (IJELS), 2020)
Motherhood is seen as one of the essential aspects in a humans life. Although several values concerning motherhood is cross-cultural, its representation varied from time to time upon locations and cultures. Deriving from this line of thought, this paper compares the differing portrayal of motherhood from Asian and African literature. Undertaking the library studies, this article illustrates the depictions of motherhood and seeks to underline the reasoning why it is manifested through the selected literary works. The novels employed as the objects of study are The Joys of Motherhood by Buchi Emecheta and Ibuk by Iwan Setyawan. The finding extrapolates a global conception towards motherhood and how it is presented. It is concluded that the depiction of motherhood in the novels is employed to maintain a social construction that privilege patriarchy. The African motherhood may be different than what they call Asian motherhood. Yet mothers, no matter where they are will always focus on their childrens well-doing.